2015
DOI: 10.1097/md.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival Outcomes of Laparoscopic Versus Open Gastrectomy for Gastric Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 64 publications
1
21
0
1
Order By: Relevance
“…Additionally, we grouped the cancer types as EGC and AGC to compare LTG and OTG more precisely. In a previous meta-analysis, mixed data of gastrectomy type data (distal, proximal, and total) and blended data of tumor stage (AGC and EGC) prevented an accurate comparison between LTG and OTG [47,48]. Furthermore, we matched confounding factors including the lymph node dissection method and lymph node metastasis ratio that might influence long-term surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we grouped the cancer types as EGC and AGC to compare LTG and OTG more precisely. In a previous meta-analysis, mixed data of gastrectomy type data (distal, proximal, and total) and blended data of tumor stage (AGC and EGC) prevented an accurate comparison between LTG and OTG [47,48]. Furthermore, we matched confounding factors including the lymph node dissection method and lymph node metastasis ratio that might influence long-term surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the oncological safety of laparoscopic surgery remains to be confirmed by phase III randomized trials; therefore, we will focus on the long‐term outcomes of on‐going clinical trials . Indeed, some reliable observational studies have reported the non‐inferiority of the oncological outcomes of LDG compared with ODG . We believe that this shift toward laparoscopic surgery will persist for some time, given the benefits associated with less‐invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The long-standing discussion regarding the oncological safety of minimally invasive access was addressed in recent meta-analyses that clearly showed that it is non-inferior to open gastrectomy. In centers that routinely perform this procedure laparoscopically, the number of lymph nodes harvested and the R0 resection rate are comparable [10,19,20]. It is rather the experience of the surgeon and the center that influences clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%